Mobilising different conversations about global justice in education: toward alternative futures in uncertain times - Andreotti, Vanessa; Stein, Sharon; Sutherland, Ali; Pashby, Karen; Susa, Rene; Amsler, Sarah (Centre for Global Education, 2018)
In this article we present four social cartographies with the intention to contribute to different conversations about global justice and education. The cartographies aim to invite curiosity, depth, reflexivity, openness, and the expansion of sensibilities as we engage with different analyses and possibilities for global change. We start with a review of HEADS UP, a social cartography that maps recurrent patterns of representation and engagement commonly found in narratives about poverty, wealth, and global change in North-South engagements and local engagements with diverse populations. We then describe the HOUSE, a social cartography that presents one way of diagnosing current crises and their multiple, overlapping dimensions. The third cartography, the TREE, makes a distinction between what is offered by different layers of analyses of social problems in terms of doing, knowing, and being. The last cartography, EarthCARE, is presented as a framework for global justice education, which emphasises the integration and entanglement of different dimensions of justice, including ecological, affective, relational, cognitive, and economic dimensions. The four social cartographies address different dimensions of the challenges of mobilising development and global education in socially complex and politically uncertain times.